2023
DOI: 10.1113/jp283836
|View full text |Cite
|
Sign up to set email alerts
|

A molecular signature defining exercise adaptation with ageing and in vivo partial reprogramming in skeletal muscle

Abstract: Exercise promotes functional improvements in aged tissues, but the extent to which it simulates partial molecular reprogramming is unknown. Using transcriptome profiling from (1) a skeletal muscle‐specific in vivo Oct3/4, Klf4, Sox2 and Myc (OKSM) reprogramming‐factor expression murine model; (2) an in vivo inducible muscle‐specific Myc induction murine model; (3) a translatable high‐volume hypertrophic exercise training approach in aged mice; and (4) human exercise muscle biopsies, we collectively defined exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 166 publications
3
50
0
Order By: Relevance
“…DNA methylation patterns are used in epigenetic clocks to accurately predict DNA methylation age (mDNAge). Using the Horvath Clock and Developmental Muscle Clock, the present study by Jones III et al (2022) found mDNAge to be significantly lower in PoWeR (progressive weighted wheel running)-trained vs. sedentary aged female mice. These findings suggest that exercise can reverse at least some of the muscle-related effects of ageing at the DNA methylation level, further reinforcing exercise as an important factor of healthy ageing.…”
Section: Epigenetics and Anti-ageingmentioning
confidence: 47%
See 4 more Smart Citations
“…DNA methylation patterns are used in epigenetic clocks to accurately predict DNA methylation age (mDNAge). Using the Horvath Clock and Developmental Muscle Clock, the present study by Jones III et al (2022) found mDNAge to be significantly lower in PoWeR (progressive weighted wheel running)-trained vs. sedentary aged female mice. These findings suggest that exercise can reverse at least some of the muscle-related effects of ageing at the DNA methylation level, further reinforcing exercise as an important factor of healthy ageing.…”
Section: Epigenetics and Anti-ageingmentioning
confidence: 47%
“…Jones III et al. (2022) verified these results in human muscle, where they showed that several mitochondrial transcripts that were downregulated by OKSM and endurance training in mice were also downregulated in the muscle of endurance trained females compared to age‐matched sedentary controls. The functional relevance of this downregulation of mitochondrial transcripts in the context of healthy ageing remains unknown.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations